1975
DOI: 10.1159/000208090
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Crisis in a Patient with Chronic Lymphatic Leukemia

Abstract: A case of chronic lymphatic leukemia terminating in a lymphoblastic crisis is described. The small lymphocytes were demonstrated to be B cells, they carried immunoglobulins on their surface and formed EAC rosettes. The lymphoblasts had no immunoglobulins on their surface and only 18% of them formed EAC rosettes, none formed E rosettes. The lymphoblasts could be either immature B cells or Null cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…More over, in 1 patient these authors showed that membrane-bound Ig of the small lympho cytes and of the lymphoblastic cells showed the same antibody activity, providing defini tive evidence that both types of proliferating cells originated from the same clone. The results are different from those obtained by Klajman et al [8] …”
Section: Methodscontrasting
confidence: 99%
See 3 more Smart Citations
“…More over, in 1 patient these authors showed that membrane-bound Ig of the small lympho cytes and of the lymphoblastic cells showed the same antibody activity, providing defini tive evidence that both types of proliferating cells originated from the same clone. The results are different from those obtained by Klajman et al [8] …”
Section: Methodscontrasting
confidence: 99%
“…To our knowledge, surface marker stud ies supervening on CCL in acute blast crisis were performed in only 3 cases [2,8], In such cases a direct immunofluorescence procedure was used to detect membranebound immunoglobulins. In routine practice the immunofluorescence procedure allowed a good evaluation of cell size but was un able to give more cytological details, still es sential to realize a good discrimination be tween the two cell populations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolymphocytic transformation is more frequently observed [1], followed by transfor mation into a diffuse large cell lymphoma, known as Richter's syndrome [2]. Acute lymphoblastic transfor mation of CLL is rare, although it has been reported in several instances [3][4][5][6][7][8][9][10], and only in 2 reports was blast crisis the initial manifestation of CLL [9,10], raising the question of whether transformation of CLL corresponded to a clonal evolution of the initial population of malignant lymphocytes or to a second malignancy with the emergence of a second unrelated clone of less differentiated lymphoid cells arising in a susceptible host, as already described in Richter's 1 We thank Dr. G.M. Lenoir (IARC, Lyon) for kindly revising the manuscript.…”
mentioning
confidence: 99%